CONSUMMATED REVIEW ON PROSTATITIS - AG, HARINE; M, SUMITRA; V, CHITRA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Prostatitis is an inflammatory disease, when the prostate is vulnerable to infectious stimuli like urinary pathogens, are changes in the lifestyle leads to inflammation in the prostate gland. It is a pathological state where the swelling of prostate occur to most of the men and mainly elderly. Recently, prostatitis is a dangerous threat for men almost 50% total men population. The review comprises complete information regarding prostatitis and its related complications. The compilation of the data is about the disease from classification of prostatitis, causative agents, symptoms, treatment, mitigation, natural and alternative therapy to improve the quality of life. Awareness of this disease is not known to the majority of the population when it is left untreated identification and treatment at the right time help in increase in recovering from the pathological condition of the victim to overcome.